Evaluation of metal nanocomposite polymer inclusion membranes (PIMs) for trace heavy metal extraction in natural waters - Maiphetlho, Kgomotso (My University, 2020)
The shortcomings of the conventional membranes in water applications such as low stability and the hydrophobic nature reduces the membrane productivity and lifespan. These result in expensive procedures that hinder membrane science technology. Hence, recent investigations have resulted in the synthesis of nanocomposite membranes as an alternative. In this work, silver nanocomposite polymer inclusion membranes (PIMs) were synthesized to evaluate the extraction of trace metal ions in natural waters. To characterise the PIMs, scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDX), contact angle measurements and water uptake measurements were used. The contact angle and the water uptake measurements highlighted that the introduction of the silver nanoparticles (Ag NPs) into the membrane, modified the membrane hydrophobic/hydrophilic character. The evaluation of the synthesized PIMs demonstrated that the PIMs containing Ag NPs exhibit better extraction capacity as opposed to the bare PIMs and the PIM with (40 w.t% D2EHPA, 10 w.t% Ag NPs and 50 w.t% PVC) has the optimum composition. It was then used to optimise the parameters that are important for the extraction of trace metal ions and those were sample pH 5, 1 M HNO3 of the receiving solution and 120 hrs for the extraction time. The selectivity of the nanocomposite PIM was investigated and it was found that its affinity towards a range of divalent cations (Co2+, Ni2+, Cu2+, and Cd2+) in synthetic water solutions, based on the percentage recovery factor of the extracted metal ions, follow the order; Cd 2+ (94) > Cu2+ (87) > Ni2+ (78) > Co2+ (67), where the numerical data in the brackets correspond to the percentage recovery factor of metal ion extracted from the source solution, respectively. This order can be explained by the Hard and Soft Acids and Bases Theory and the hydration energy of the metal cations. However, the stability of the PIM was still compromised during repeated cycle operations despite an improvement of hydrophilicity with introduction of Ag NPs, this was indicated by an appreciable leaching of the carrier (D2EHPA) and Ag NPs in a 4:1 ratio (identical to the ratio of these components in the original membrane). This silver nanocomposite PIM was tested in dam water. No matrix effect was observed on metal ion transport efficiency in such waters. The obtained transport efficiencies for the metal ions were Cd2+ (88), Cu2+ (80) , Ni2+ (62) , Co2+ (70) and Fe2+ (37) respectively. The newly synthesized PIM could be used for future extraction of the target metals in water systems. The designed PIM system has also the potential to be used as passive sampler for in situ extraction of the target metals in water systems. However, further studies are needed to improve the stability of both the carrier and nanoparticles in the membrane
A dissertation submitted to the Faculty of Science, in fulfilment of the requirements of the Master of Science degree, University of the Witwatersrand, Johannesburg, 2020
Keywords: Nanocomposites (Materials); Polymeric composites; Nanostructured materials